Voicing the Unvoiced and Constructing the national narrative; A critical Discourse Analysis of Shahbaz Sharif’s Speech at United Nations General Assembly - Tehseem, Tazanfal; Mehdi, Uzair; Hussain, Adnan; Nazar, Assad; Batool, Naima (ACADEMIA International Journal for Social Sciences, 2025)
The present study explores the ideological discourse structure in Shahbaz Sharif’s speech at the General assembly of United Nation Organization through the application of critical discourse analysis. It focuses to probe the hidden ideological meanings of his words phrases and sentences. Fairclough’s (1995) three dimensional framework is employed to scrutinize unequivocal and equivocal meanings of the linguistic patterns used by him. The data is driven from his speech at 79th session of UNGA delivered on 27 Oct 2024. Palestine issue, war in Ghaza and terrorism are discussed repeatedly. The burning issues which are threatening to the global are stressed in his speech. The results derived from this study manifests that peace and harmony between Muslim Ummah and the rest of the world is conditional. Seaize fire in Ghaza is the symbol of stability in Middle East. These themes are identified by the frequent use of some words and phrases to inculcate desired ideology into the minds of world’s leaders. He uplifted the voice for suppressed and unvoiced people of Palestine. The findings of this study show that language plays vital role in generating particular ideology and its effects upon of listeners and readers.